Development of a Web-based Geographic Information System for Locating Medical Practices - Andryanto Aman; Wisda Wisda; Suryadi Syamsu; Khaidir Rahman Nasir; Tatik Maslihatin; Magfirah Nur Iqlimah (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2023)
This study aims to develop a web-based Geographic Information System (GIS) for searching medical practices. The system is designed to provide the public with easy access to information on the location of medical practices in the city. The Haversine method is used to calculate the distance between the user's location and the medical practice locations, and the system displays the nearest locations on the map. The system was developed using the PHP programming language, MySQL database management system, and Google Maps API. The user interface was designed to be simple and user-friendly, with a search bar and filters for narrowing down search results. The system's feasibility was evaluated through a questionnaire answered by 20 respondents with seven questions. The average score was 84.42%, indicating that the system is highly feasible for use. The developed system is expected to facilitate the public's access to medical practices and provide a more efficient way to find the nearest doctor.